The Risk of Caution: Evidence from an Experiment - Carson, Richard T.; Graff Zivin, Joshua; Louviere, Jordan J.; Sadoff, Sally; Shrader, Jeffrey G. (Management Science, 2022)
Innovation is important for firm performance and broader economic growth. However, breakthrough innovations necessarily require greater risk taking than more incremental approaches. To understand how managers respond to uncertainty when making research and development decisions, we conducted experiments with master’s degree students in a program focused on the intersection of business and technology. Study participants were asked to choose whether to fund hypothetical research projects using a process that mirrors real-world research and development funding decisions. The experiments provided financial rewards that disproportionately encouraged the choice of higher-risk projects. Despite these incentives, most participants chose lower-risk projects at the expense of projects more likely to generate a large payoff. Heterogeneity analysis and additional experimental treatments show that individual risk preferences predict greater tolerance of high-risk projects and suggest that more appropriate decision making can be learned. Thus, for firms seeking to fund breakthrough research and development, appropriate screening and training of employees may play important roles in increasing the likelihood of success. This paper was accepted by Gustavo Manso, finance. Funding: This work was supported by the National Science Foundation [Grant SBE-1561257]. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2021.4292 .